T Cell Lymphoma and Leukemia in Severe Combined Immunodeficiency Pigs following Bone Marrow Transplantation: A Case Report - Powell, Ellis J.; Graham, Jared; Ellinwood, N. M.; Hostetter, Jesse; Yaeger, Michael; Ho, Chak-Sum; Gault, Lynden; Norlin, Veronica; Snella, Elizabeth N.; Jens, Jackie; Waide, Emily H.; Boettcher, Adeline N.; et al. (Frontiers in Immunology, 2017)
After the discovery of naturally occurring Severe Combined Immunodeficiency (SCID) within a selection line of pigs at Iowa State University (ISU), we found two causative mutations in the Artemis gene: haplotype 12 (ART12) and haplotype 16 (ART16). Bone marrow transplants (BMTs) were performed to create genetically SCID and phenotypically immune competent breeding animals to establish a SCID colony for further characterization and research utilization. Of nine original BMT transfer recipients, only four achieved successful engraftment. At approximately eleven months of age, both animals homozygous for the ART16 mutation were diagnosed with T-cell lymphoma. One of these ART16/ART16 recipients was a male who received a transplant from a female sibling; the tumors in this recipient consist primarily of Y chromosome-positive cells. The other ART16/ART16 animal also presented with leukemia in addition to T-cell lymphoma, while one of the ART12/ART16 compound heterozygote recipients presented with a nephroblastoma at a similar age. Human Artemis SCID patients have reported cases of lymphoma associated with a ‘leaky’ Artemis phenotype. The naturally occurring Artemis SCID pig offers a large animal model more similar to human SCID patients and may offer a naturally occurring cancer model and provides a valuable platform for therapy development.